ANALYSIS OF THE STUDENTS' PEDAGOGICAL CONTENT KNOWLEDGE AND CONTENT KNOWLEDGE IN MATHEMATICS LEARNING - Tina Sri Sumartini (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:Lack of Pedagogical Content Knowledge (PCK) and Content Knowledge (CK) of a teacher is a problem in the implementation of mathematics learning. There were various opinions about the correlation between PCK and CK of teacher's knowledge. Therefore, this study aims to analyze the correlation between them to the students of Mathematics Education as prospective mathematics teachers. The method used was a mix-method to determine the inferential correlation and to investigate deeply. The sampling technique used was purposive sampling by taking 33 students majoring in Mathematics education at Institut Pendidikan Indonesia. The results of the study indicated that there was a significant correlation between the students' PCK and CK as prospective teachers. PCK and CK were an integral part of teacher competence in teaching Mathematics. This study confirmed that the Mathematical beliefs of prospective teachers need serious attention. The implication in this study provided a statement about the importance of constructivism learning in the development of students' PCK and CK.Abstrak:Kurangnya Pedagogical Content Knowledge (PCK) dan Content Knowledge (CK) seorang guru menjadi masalah dalam pelaksanaan pembelajaran matematika. Terjadi perbedaan pendapat tentang korelasi keduanya dalam struktur pengetahuan guru. Oleh karena itu dilakukan penelitian untuk menganalisis korelasi antara PCK dan CK pada mahasiswa jurusan Ppendidikan Matematika sebagai calon guru Matematika. Metode yang digunakan adalah mix-method untuk mengetahui korelasi secara inferensial dan menganalisis lebih dalam secara kualitatif. Teknik sampel yang digunakan yaitu puposive sampling dengan mengambil sampel sebanyak 33 mahasiswa jurusan pendidikan matematika di Institut Pendidikan Indonesia. Hasil dari penelitian menunjukkan bahwa terdapat korelasi yang signifikan antara PCK dengan CK mahasiswa sebagai calon guru. PCK dan CK merupakan satu kesatuan dari kompetensi guru dalam mengajar Matematika. Penelitian ini menegaskan bahwa keyakinan Matematis calon guru perlu mendapat perhatian yang serius. Implikasi dalam penelitian ini memberikan pernyataan tentang pentingnya pembelajaran kontruktivisme dalam pengembangan PCK dan CK mahasiswa.